Choosing justice : an experimental approach to ethical theory - Frohlich, Norman (University of California Press, 1992)
This book presents an entirely new answer to the question: "What is fair?" In their radical approach to ethics, Frohlich and Oppenheimer argue that much of the empirical methodology of the natural sciences should be applied to the ethical questions of fairness and justice.
Keywords: Distributive justice.; Income distribution.; Social choice.; Justice distributive.; Revenu -- Répartition.; Choix collectif.; BUSINESS & ECONOMICS -- Business Ethics.; BUSINESS & ECONOMICS -- Economics -- General.; BUSINESS & ECONOMICS -- Reference.; PHILOSOPHY / Ethics & Moral Philosophy; Distributive justice; Income distribution; Social choice